PDGF regulates the actin cytoskeleton through hnRNP-K-mediated activation of the ubiquitin E(3)-ligase MIR - Nagano, Kohji (2006)
PDGF is a potent chemotactic mitogen and a strong inductor of fibroblast motility. In Swiss 3T3 fibroblasts, exposure to PDGF but not EGF or IGF-1 causes a rapid loss of actin stress fibers (SFs) and focal adhesions (FAs), which is followed by the development of retractile dendritic protrusions and induction of motility. The PDGF-specific actin reorganization was blocked by inhibition of Src-kinase and the 26S proteasome. PDGF induced Src-dependent association between the multifunctional transcription/translation regulator hnRNP-K and the mRNA-encoding myosin regulatory light-chain (MRLC)-interacting protein (MIR), a E(3)-ubiquitin ligase that is MRLC specific. This in turn rapidly increased MIR expression, and led to ubiquitination and proteasome-mediated degradation of MRLC. Downregulation of MIR by RNA muting prevented the reorganization of actin structures and severely reduced the migratory and wound-healing potential of PDGF-treated cells. The results show that activation of MIR and the resulting removal of diphosphorylated MRLC are essential for PDGF to instigate and maintain control over the actin–myosin-based contractile system in Swiss 3T3 fibroblasts. The PDGF induced protein destabilization through the regulation of hnRNP-K controlled ubiquitin -ligase translation identifies a novel pathway by which external stimuli can regulate phenotypic development through rapid, organelle-specific changes in the activity and stability of cytoskeletal regulators.